2017
DOI: 10.1186/s12862-017-0925-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive transcriptomic analysis of Tibetan Schizothoracinae fish Gymnocypris przewalskii reveals how it adapts to a high altitude aquatic life

Abstract: BackgroundUnderstanding the genetic basis of adaptation to high altitude life is of paramount importance for preserving and managing genetic diversity in highland animals. This objective has been addressed mainly in terrestrial fauna but rarely in aquatic animals. Tibetan Schizothoracinae fish is the ideal model system in evolutionary biology, carrying key insights into evolutionary genetics of speciation and adaptation at high altitude. Gymnocypris przewalskii is the newly formed Schizothoracinae fish species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 58 publications
(90 reference statements)
10
68
0
Order By: Relevance
“…Over the past few years, transcriptome-based assembly approach enables comparative genomics studies widely employed in many Tibetan endemic organisms to provide insights of highland adaptation [15][16][17]23,40,41]. Unlike whole genome data, although transcriptome sequencing is an effective and accessible approach to initiate comparative genomic analyses on non-model organisms [28], it still can not cover the whole protein coding gene repertoire of one species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, transcriptome-based assembly approach enables comparative genomics studies widely employed in many Tibetan endemic organisms to provide insights of highland adaptation [15][16][17]23,40,41]. Unlike whole genome data, although transcriptome sequencing is an effective and accessible approach to initiate comparative genomic analyses on non-model organisms [28], it still can not cover the whole protein coding gene repertoire of one species.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomics approaches have the power to facilitate investigation of the genomic basis of evolution and adaptation [14]. Recent comparative genomics studies based on transcriptomic data of several Schizothoracine species have identified a number of candidate genes that underwent positive selection during the longterm adaptive processes to harsh environments on the Tibetan Plateau, such as hypoxia [15] and low temperature [16,17]. Notably, an increasing number of lakes are existing or towards saline and alkaline due to the geological evolution and global climate changes on the Tibetan Plateau [3,18].…”
Section: Introductionmentioning
confidence: 99%
“…Only RNA with high quality (RNA Integrity Number > 7) were used for cDNA synthesis and amplification. Libraries were prepared with the Nextera XT DNA Library Prep Kit (Illumina, CA, USA) using ~350-bp inserted fragments for transcriptome sequencing as previously described (Tong, Tian, et al 2017;Tong, Fei, et al 2017). Libraries were individually barcoded and run on a single lane of an Illumina NovaSeq (Novogene, CA, USA) yielding 150-bp paired-end reads.…”
Section: Expression Profiles Of Rapidly Evolving Genes In Four Tissuementioning
confidence: 99%
“…An increasing number of transcriptome targeted to identify abundant immune genes in fish by sampling immune-relevant tissues, such as head-kidney and spleen [21][22][23]25]. To maximize the information content of immune gene sequences, we collected two immune relevant tissues, head-kidney and spleen, plus two less relevant tissues (gills and skin) transcriptome data for assembly, which generated much more unigenes than our previous assembly versions of G. przewalskii [7,23]. In addition, compared with our previous comparative genomics study in G. przewalskii [7], we identified more immune genes…”
Section: Ichthyophthirius Multifiliis Infectionmentioning
confidence: 99%
“…Understanding how fish species adapt to the aquatic life at high altitude is an interest for both ichthyologists and evolutionary biologists [1]. As the largest and highest highland in the world with the average elevation above 4000m [2], the Tibetan Plateau imposes extremely harsh aquatic environments on endemic fish fauna [3], including hypoxia [4], chronic cold [5,6] and high salinity and alkalinity [7,8].…”
Section: Introductionmentioning
confidence: 99%